Analysis of Village Fund Management Accountability: Analisis Akuntabilitas Pengelolaan Dana Desa - Nita Anastasya; Dwi Anggraini; Khojanah Hasan (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
Village financial management is inseparable from the principle of accountability. Accountable village financial management is a system that can be accounted for, from the planning stage, implementation, administration, to village financial reporting. Village fund management is expected to encourage equitable development and provide real benefits to the community. To realize effective village fund management, competent government officials are needed and supported by adequate facilities, so that implementation can run in a directed manner and in accordance with the principles of good governance. This study discusses the accountability of fund management in Wonorejo Village, Lawang District, Malang Regency, East Java. The method used is qualitative descriptive analysis. Data analysis is carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that accountability in village fund management in Wonorejo Village has been implemented well. Village finances are managed based on the principles of transparency, accountability, and participation, and are carried out in an orderly and disciplined budget. The principle of accountability can be seen through the reporting prepared for each fiscal year and the existence of village deliberations involving all components of the community. As a follow-up, it is recommended to use online systems and application-based financial management to improve accountability and transparency of reports.